The empirical evidence base for the use of the HCR-20: A narrative review of study designs and transferability of results to clinical practice. (September 2021) - Challinor, Alexander; Ogundalu, Abisola; McIntyre, Jason C.; Bramwell, Vicky; Nathan, Rajan
Abstract: The HCR-20, a widely used method of assessing and managing risk, relies on the structured professional judgement approach. This paper reports a narrative literature review of the HCR-20 studies to explore the applicability of the study results to the use of the HCR-20 in clinical practice. From a literature search using terms "HCR-20" and "HCR 20", 206 papers were included. Of studies using the HCR-20 version 2 ( n = 191), 92% ( n = 176) relied on variables based on scores derived by adding item scores, and 50% ( n = 95) tested the HCR-20 using predictive validity methodology. Of the HCR-20 version 3 studies ( n = 21), the "presence of risk factors" step was the most commonly examined ( n = 18, 86%), but 2 of the 7 steps ("scenario planning" and "management") were not examined at all. Amongst those studies whose primary focus was on the HCR-20, 67% ( n = 64/95) did so by assessing the predictive validity of the tool. Only one employed a design to test whether the use of the HCR-20 affected violence rates. The predominant study design provides support for the use of the HCR-20 as an actuarial tool, and there is limited empirical evidence in support of its effectiveness as a structured professional judgement approach to the assessment and management of the risk of violence.